An improved lean assessment based on employee perception. Issue 4 (5th January 2021) - Huang, Zhengyin; Harris, Gregory; Loyd, Nicholas
Abstract : Purpose: The Toyota Production System has been studied for its business success for several decades. Many companies have tried to imitate but have not achieved Toyota-like results. Failure in the ability to replicate Toyota's supportive culture has been suggested as a cause for the lack of success. Studies on lean implementation have been conducted from external views focusing on visible indicators, but few seek the employee's perception of lean initiatives. The authors propose a Toyota Production System – Toyota Way (TPS-TW) model approach using employee perception and quantitative performance metrics. Design/methodology/approach: This research represents an improvement of a lean assessment instrument using quantifiable performance metrics for validation and testing it in the Chinese automotive industry. A survey was developed and executed in the Chinese automotive industry with participants involved with lean implementation. Experts helped examine the content validity, and reliability analysis was used to study the structure of the assessment instrument and evaluate internal consistency. Confirmatory factor analysis and structured equation modeling were used to test the construct validity. Finally, survey results and actual performance were analyzed. Findings: The results of this research validated the TPS-TW model and assessment instrument in the Chinese automotive industry. Originality/value: This research validates an employee perception survey that can be utilized by organizations to understand the state of their lean implementation. The research supports the use of employee perception to reflect the reality of a lean initiative and proves the TPS-TW model is an effective theoretical framework for assessment.